Learning Interest and Gender Differences in Indonesian High Schools: Their Influence on Understanding the Concepts of Work and Energy - Safitri, Yustina; Kusairi, Sentot (Journal of Social Work and Science Education, 2025)
This study examines the influence of gender and learning interest (cognitive [CI] and emotional [EI]) on high school students' conceptual understanding of Work and Energy in physics. A quantitative correlation design was employed with 64 students. A 21-item conceptual test and a 16-item Likert-scale interest questionnaire (7 CI, 9 EI) were administered. Data were analyzed using descriptive statistics, Mann-Whitney U test (gender), and Spearman correlation (interest). Only 28% of students fully understood the concepts, while 42% did not. No gender differences were found, but interest significantly correlated with conceptual understanding (*r* = 0.36, *p* < 0.05). Conclusion: Interest, not gender, predicts conceptual understanding in physics. The study uniquely integrates cognitive and emotional interest dimensions while assessing gender effects. Physics instruction should enhance interest through real-life contexts to improve engagement and learning. Provides empirical evidence that fostering student interest is crucial for conceptual mastery in physics.